2021
DOI: 10.1111/jnc.15513
|View full text |Cite
|
Sign up to set email alerts
|

Serum beta‐secretase 1 (BACE1) activity increases in patients with mild cognitive impairment

Abstract: Beta-secretase 1 (BACE1) is considered as the key enzyme in amyloidβ formation.Previous works suggest that high BACE1 activity may be present in brain, cerebrospinal fluid and serum of patients with late-onset Alzheimer's disease (LOAD) as well as mild cognitive impairment (MCI). Therefore, we evaluated whether serum BACE1 activity increases in MCI patients and is associated with the progression from MCI to dementia. BACE1 activity was measured in the serum of 259 MCI patients (162 amnestic-aMCI, 97 non-amnest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(60 reference statements)
2
2
0
Order By: Relevance
“…More intriguingly, a recent longitudinal study has shown that plasma BACE1 level is associated with progressive axonal damage/neurodegeneration in AD critical brain region, already in cognitively and physically healthy individuals (at risk of AD) [ 6 ]. Consistently, we have also observed an association between high BACE1 and the presence of brain atrophy in aMCI [ 5 ].…”
supporting
confidence: 81%
See 2 more Smart Citations
“…More intriguingly, a recent longitudinal study has shown that plasma BACE1 level is associated with progressive axonal damage/neurodegeneration in AD critical brain region, already in cognitively and physically healthy individuals (at risk of AD) [ 6 ]. Consistently, we have also observed an association between high BACE1 and the presence of brain atrophy in aMCI [ 5 ].…”
supporting
confidence: 81%
“…In other words, for MCIs with pronounced cognitive symptoms, the impact of tauopathy and inflammation may be dominant and mask the contribution of BACE1 in the progression to the disease. Apparently, the results we obtained by Cox model (median follow up of 32 months) do not support the use of serum BACE1 activity as prediction biomarker for AD and dementia in general [ 5 ]. However, it must be underscored that our final sample was definitely underpowered for this kind of analysis.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Increasing evidences show the potential of serum/plasma BACE1 levels as an early biomarker of cognitive decline [ 11, 12 ]. The increase of almost 61% of BACE1 serum activity we achieved, is in line with 53% increase in MCI and 68% in AD showed by Shen and co-authors [ 11 ], and of 30% in late onset AD reported by Zuliani et al (2021) [ 13 ].…”
Section: Discussionsupporting
confidence: 91%
“…General and neuropsychological examinations, including standardized Mini-Mental State Examination (MMSE [ 25 ], upon permission from PAR was granted to use this scale), geriatric depression scale, and CDR, were carried out as previously described [ 26 ]. The functional status was evaluated by basic and instrumental activities of daily living (BADL and IADL, respectively) [ 27 ]. Demographic and medical history data (e.g., hypertension, CHD, stroke, diabetes, chronic obstructive pulmonary disease) were collected by trained personnel [ 27 ].…”
Section: Methodsmentioning
confidence: 99%